Sistem Penyimpanan Arsip Di Ruangan Bimas Kristen Di Kantor Kementerian Agama Kabupaten Luwu - cristina totong; Delmi Delmi (Institut Agama Kristen Negeri Toraja, 2023)
Abstract: The archive storage system for Christian religious counseling and Christianreligion teachers at the Luwu Regency Ministry of Religion office is not tidy, so it is difficultto find when needed. Archive storage that is not in accordance with procedures makes itdifficult for employees and owners to find the required archives. How to store archives mustbe done according to storage procedures that have been arranged so that when neededthey are easy to find. However, what happened at the office of the Ministry of Religion ofLuwu Regency, especially in the Christian community guidance room, was a small andinadequate room so that the lack of facilities made employees store various files in piles.But with advances in technology, archive storage can be done in the form of files on acomputer with the aim of minimizing the accumulation of files in the office of the Ministryof Religion of Luwu Regency, especially the Christian community guidance room.Keywords: Archive Storage SystemAbstrak: Sistem penyimpanan arsip penyuluhan agama Kristen dan guru agama Kristendi kantor Kementerian Agama Kabupaten Luwu tidak rapi, sehingga saat diperlukan sulitditemukan. Penyimpanan arsip yang tidak sesuai prosedur membuat pegawai danpemilik kesusahan untuk mencari arsip yang diperlukan. Cara menyimpan arsip harusdilakukan sesuai prosedur penyimpanan yang sudah diatur supaya saat diperlukanmudah untuk ditemukan. Tetapi yang terjadi di kantor Kementerian Agama KabupatenLuwu khususnya dalam ruangan bimbingan masyarakat Kristen dengan ruangan yangkecil serta tidak memadai hingga minimnya fasilitas membuat pegawai menyimpanberbagai berkas hanya dengan ditumpuk. Tetapi dengan kemajuan teknologi,penyimpanan arsip bisa dilakukan dengan bentuk file di komputer yang tujuannyameminimalisir penumpukan berkas di kantor Kementerian Agama Kabupaten Luwukhususnya ruang bimbingan masyarakat Kristen.Kata Kunci : Sistem Penyimpanan Arsip